Prestigious Sites of Karakalpakstan - Bekbosinov Yesbosin Bekpolatovich (Researchparks Publishing, 2023)
Karakalpakstan, located in Uzbekistan, is home to several historical sites that showcase the region's rich cultural heritage. Our main goal is to protect and maintain this historical site in its original state and ensure its transmission to future generations through raising public awareness about its significance.